IMPLEMENTATION OF ABACUS MEDIA TO IMPROVE BASIC MATHEMATICS LEARNING OUTCOMES IN VII GRADE BLIND ABK STUDENTS AT SLB A YAKETUNIS - Firmawati Firmawati; Syariful Fahmi (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
Mathematics is an abstract science, and it makes the students difficulties in completing a matter of mathematics, one of the materials about addition and subtraction operations. The research aims to test abacus media's use to improve basic mathematics learning outcomes for blind exceptional children. This research used the SSR (Single Subject Research) method. The subject of this research is Class VII blind. Data collection techniques used learning outcomes tests, interviews, and student responses during the treatment implementation. The data obtained were analyzed through descriptive statistics and displayed in graphical form. Technical analysis of the data used the analysis of conditions and analysis between conditions using AB research design. The results showed that the Baseline phase had a length of conditions for three days and the Intervention phase had a length of conditions for five days. The ability addition and subtraction operations results are shown by increasing the score at the mean level. Students' mean level increased from before being given treatment from 48,33 to 88 after being given treatment. Based on the research and discussion results, Abacus media can improve student learning outcomes and subtraction operations material in the seventh-grade class VIIA blind Exceptional Children in A Yaketunis.